2020
DOI: 10.36312/jisip.v4i4.1534
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students Writing Anecdote Skill Through Scientific Method In The First Grade Students Of SMAN 3 Praya

Abstract: This study was aimed to know the writing anecdote skill in the first grade students of SMAN 3 Praya, the researcher chose the anecdote as the material because there are 13 kind of text in English, but anecdote is rarely taught by the teacher whereas anecdote is interesting story about a real incident or person and the students may interested when they learn about anecdote text. This research used scientific method, The term “Scientific Method” gained its popularity in the field of education in Indonesia when C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to Yulandari (2020), writing can be an effective tool for the development of academic language proficiency as learners have to explore advanced lexical or syntactic expression in their written work. In the process of learning to write, however, it is often found that students still experience difficulties in writing, they are faced with feelings of inferiority, overcome by feelings of fear to convey story ideas that they have experienced themselves or which are only imagination.…”
Section: Introductionmentioning
confidence: 99%
“…According to Yulandari (2020), writing can be an effective tool for the development of academic language proficiency as learners have to explore advanced lexical or syntactic expression in their written work. In the process of learning to write, however, it is often found that students still experience difficulties in writing, they are faced with feelings of inferiority, overcome by feelings of fear to convey story ideas that they have experienced themselves or which are only imagination.…”
Section: Introductionmentioning
confidence: 99%